Virtual Elements for the Reissner‐Mindlin plate problem. Issue 4 (21st February 2018) - Chinosi, Claudia
Abstract : In this work, we present a virtual element method for the approximation of the plate bending problem in the Reissner‐Mindlin formulation. The proposed method follows the MITC approach of the FEM context. We construct a family of VEM spaces with arbitrary degree of accuracy that satisfies the conditions of the MITC philosophy. We perform some numerical tests which allow us to assess the convergence and the robustness of the method.